The effect of glysemic control on myocardial performance index in patients with type 2 diabetes mellitus - (:unkn) unknown (My University, 2011)
Amaç: Tip 2 diyabette, kötü glukometabolik kontrol kalp yetersizliği riskini arttırır. Çalısmamızda, kalp hastalığı olmayan tip 2 diyabetlilerde glisemik kontrol- miyokard performans iliksisini (MPI) arastırmayı amaçladık. Gereç ve Yöntem: Tip 2 diyabetli 42 hastada sol ventrikül sistolik ve diastolik fonksiyonları standart transtorasik ve doku Doppler ekokardiyografi ile saptandı. Glisemik kontrol; açlık plazma glukozu(APG) ve hemoglobin A1c(HbA1c) ile ifade edildi. Bilinen kardiyovasküler, pulmoner sistem ile diyabet dışı endokrin hastalıklar, anemi, angina pektoris ve dispne anamnezi ile periferik ödem olan hastalar çalışmaya alınmadılar. Bulgular: 37-57 yas arasında, %40,5'i erkek, %59,5'u kadın toplam 42 hasta çalışmaya alındı. Hem HbA1c ile MPI arasında, hem de APG ile MPI arasında bir ilişki saptanmadı. Aynı zamanda glisemik kontrol ile EF arasında da bir ilişki yoktu. Sonuç: Kalp hastalığı olmayan diyabetiklerde kardiyak fonksiyon bozukluğu gösterilmistir ve açlık plazma glukozu ile konjestif kalp yetersizliği riski ilişkilidir. MPI; hem sağ ventrikül hem sol ventrikül fonksiyonlarını gösteren bir Dopler indeksidir. Çalışmamızda, bilinen kalp hastalığı olmayan diyabetik hastalarla sağlıklı kontrol grubu arasında sol ventrikül fonksiyonları bakımından fark saptamadık; glisemik kontrol ile EF ve MPI ile ifade edilen sol ventrikül fonksiyonu arasında bir ilişki yoktu.

Purpose: Type 2 diabetes mellitus (DM) and poor glucometabolic control increase the risk of developing the heart failure. We aimed to investigate association between glysemic control and left ventricle myocardial performance index (MPI) in patients with type 2 DM and without known cardiac disease. Material and Method: Left ventricular functions using conventional transtorasic and tissue doppler echocardiography were evaluated in 42 patients. Glysemic control is expressed as fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c). The exclusion criteria were known cardiovascular system diseases, pulmonary diseases, endocrine diseases; anemia, history of angina pectoris, dyspnea, and peripheral edema. Results: Fourty two patients, men (40.5%) and women (59.5%) aged 37-57 years were included. There was no correlation between HbA1c and MPI, and FPG and MPI. Moreover, there was no correlation between glysemic control and ejection fraction (EF). Conclusion: It was shown that ventricular abnormalities in diabetics without known heart disease and also elevated fasting glucose level are associated with risk of congestive heart failure. The Doppler index, MPI, allows both sistolic and diastolic performance to be estimated. In our study, left ventricular functions were similar between healthy controls and diabetics without known cardiac disease. We could not find any relationship between glysemic control and left ventricular dysfunction expressed by EF and MPI. Top Abstract Introduction Methods Results Disscussion References
Tip 2 diyabetli hastalarda glisemik kontrolün miyokard performans indeksine etkisi
Keywords: Genel ve Dahili Tıp